The Correlation between Vocabulary Complexity Mastery and Students’ Speaking Skills - Sukendra, Irmala; Forsia, Lastry; Dzikri, Maulana Syarif (Indonesian Journal of English Language Studies (IJELS), 2023)
This study focuses on the correlation between vocabulary complexity mastery and students’ speaking skills. The purpose of this research was to find out whether vocabulary complexity mastery can influence students’ speaking skills. In finding out the correlation between variables and the degree of correlation, the researcher used quantitative research methods with a correlational research design. This study involved 25 students who were in class XI Nursing major. In collecting research data, the researcher used a vocabulary complexity test (PVLT) of 30 questions. Meanwhile, to find out the speaking skill, the researcher used speaking instruction (Role-play; Cued Task) which involves three assessors. Based on the results of the analysis of the calculation through SPSS, the calculation results obtained the value of Sig. (2-tailed) = 0.0000.005, which indicates that Ha is accepted and H0 is rejected. Therefore, there is a significant correlation between vocabulary complexity mastery and students’ speaking skills.